Vitamin-D deficiency is associated with chronic bacterial colonisation and disease severity in bronchiectasis. Issue 1 (16th October 2012) - Chalmers, James D; McHugh, Brian J; Docherty, Catherine; Govan, John R W; Hill, Adam T
Abstract : Introduction: Vitamin-D deficiency has been linked to an increased risk of respiratory infections. The objective of this study was to determine the frequency and clinical importance of vitamin-D deficiency in patients with bronchiectasis. Methods: 25-hydroxyvitamin-D was measured by immunoassay in 402 stable patients with bronchiectasis. Patients were classified as vitamin-D deficient (serum 25-hydroxyvitamin-D <25 nmol/l), insufficient (25 nmol/l–74 nmol/l) or sufficient (≥75 nmol/l). Disease severity was assessed, including exacerbation frequency, measurement of airway inflammatory markers, sputum bacteriology and lung function over 3 years follow-up. Results: 50% of bronchiectasis patients were vitamin-D deficient, 43% insufficient and only 7% sufficient. This compared to only 12% of age and sex matched controls with vitamin-D deficiency (p<0.0001). Vitamin-D deficient patients were more frequently chronically colonised with bacteria (p<0.0001), 21.4% of vitamin-D deficient subjects were colonised with Pseudomonas aeruginosa compared to 10.4% of insufficient patients and 3.6% of sufficient patients, p=0.003. Vitamin-D deficient patients had lower FEV1 % predicted (p=0.002), and more frequent pulmonary exacerbations (p=0.04). Vitamin-D deficient patients had higher sputum levels of inflammatory markers and demonstrated a more rapid decline in lung function over 3 years follow-up. Defects in neutrophil function and assessment of airway LL-37 levels did not provide a mechanistic explanation for these findings. Vitamin-D deficient patients had, however, higher levels of Vitamin-D Binding Protein in sputum sol. Conclusions: Vitamin-D deficiency is common in bronchiectasis and correlates with markers of disease severity. The mechanism of this association is unclear.